Prognostic Value of Standard Coronary Computed Tomography Angiography Reporting System (CAD-RADS) - Altay, Sedat (Indian Journal of Radiology and Imaging, 2021)
Aims This study evaluated the clinical prospects of Coronary Artery Disease—Reporting and Data System (CAD-RADS) scoring in coronary computed tomography angiography (CTA). The aim of the study was to determine the guidance value of CAD-RADS scoring in patient follow-up after CTA.Methods and Materials Reports of cases reported between 2010 and 2013 were reevaluated with CAD-RADS scoring. Clinical risk analysis was performed with initial forms of anamnesis. Clinical follow-up was performed on 7 to 10 years (mean: 8 years, 4 months) hospital records. Univariate and multivariate Cox modeling was performed with Kaplan–Meier method to define the relationship between clinical (age, gender, diabetes mellitus, hypertension, smoking, family history) and CAD-RADS variables, and for risk analysis based on these causes. Cox proportional-hazards analysis results were presented as a hazard ratio with a 95% confidence interval. CAD-RADS scores were evaluated as meaningful determinants of univariate and multivariate Cox proportional survival analysis.Results Totally, 359 cases were evaluated in the study. Severe coronary pathology development rate was observed as CAD-RADS 0to 1%, CAD-RADS 1 to 3%, CAD-RADS 2 to 4%, CAD-RADS 3 to 9%, CAD-RADS 4A to 21%, 4B to 25%, CAD-RADS 5 to 50%. There were no coronary artery deaths in CAD-RADS 1,2,3 cases in 10 years of follow-up. Two cases with CAD-RADS 4 A score, three cases with 4 B score, and four patients with CAD-RADS 5 had a history of death as a result of coronary disease.Conclusions The cases with a high risk of side effects with CAD-RADS scores were clearly shown. CAD-RADS score accurately identifies risks in postimaging follow-up and is a reliable reporting system in the required treatment planning.
Keywords: CAD-RADS; computed tomography angiography; coronary artery disease; prognosis